On Selfish and Altruistic Coalition Formation in Cognitive Radio Networks - DA SILVA, LUIZ (IEEE, 2010)
We formulate the sensing-throughput tradeoff problem for distributed cognitive radio (CR) networks as a coalition formation game. Formation of coalitions enables the CRs to increase their achievable throughput, under the detection probability constraint, while also taking into account the overhead in sensing reports combining. In the proposed game, CRs form coalitions either to increase their individual gains (sel?sh coalition formation) or to maximize the overall gains of the group (altruistic coalition formation). We ?nd that the altruistic coalition formation solution yields signi?cant gains in terms of reduced average false alarm probability and increased average throughput per CR as compared to the sel?sh and non-cooperative solutions. Given a target detection probability for a coalition, we also propose an SNR dependent target detection probability for individual CRs in a coalition and analyze its impact on the average throughput per CR. Finally, we also analyze the impact of the cost of distributed cooperative sensing on the cooperative strategies of CRs.
PUBLISHED
Keywords: cognitive networks; cognitive radio; coalitional game theory; spectrum sensing